Β-Sitosterol and stigmasterol ameliorate dextran sulfate sodium-induced colitis in mice fed a high fat Western-style diet. Issue 11 (16th October 2017) - Feng, Simin; Dai, Zhuqing; Liu, Anna; Wang, Hong; Chen, Jayson; Luo, Zisheng; Yang, Chung S.
Abstract : Stigmasterol and β-sitosterol ameliorate DSS-induced colitis in mice by suppressing the activation of NF-κB; stigmasterol also downregulates COX-2 and CSF-1. Abstract : Phytosterols, the plant analogues of cholesterol, widely occur in the human diet. In this study, we investigated and compared the effects of stigmasterol and β-sitosterol (both with purities ≥95%) on dextran sulfate sodium (DSS)-induced colitis in C57BL/6J male mice fed a high fat Western-style diet. Mice treated with DSS developed severe mucosal colitis, with a marked distortion and crypt loss of colonic surface epithelium. Both β-sitosterol and stigmasterol significantly inhibited colon shortening, lowered fecal hemoglobin content, and reduced the severity of colitis in the middle and distal colon ( p < 0.05). These phytosterols also significantly suppressed the activation of nuclear factor-kappa B. They also significantly decreased colony stimulating factor-1 and the nuclear translocation of inflammatory master regulator nuclear factor-kappa B. Stigmasterol significantly lowered the colonic inflammation score and the expression of cyclooxygenase-2 and colony stimulating factor-1, while β-sitosterol was less or not effective. These results suggest that dietary intake of stigmasterol and β-sitosterol ameliorates colitis. Such activities of stigmasterol and β-sitosterol in humans remain to be investigated.